2012
DOI: 10.1111/j.1349-7006.2012.02254.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of metachronous second primary cancers in Osaka, Japan: Update of analyses using population‐based cancer registry data

Abstract: Cancer survivors are at excess risk of developing second primary cancers, but the precise level of risk in Japanese patients is not known. To investigate the risk of survivors developing second primary cancers, we conducted a retrospective cohort study using data from the Osaka Cancer Registry. The study subjects comprised all reported patients aged 0-79 years who were first diagnosed with cancer between 1985 and 2004 in Osaka and who survived for at least 3 months, followed-up through to December 2005. A meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
114
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(131 citation statements)
references
References 19 publications
12
114
2
3
Order By: Relevance
“…Ya que la frecuencia de ocurrencia de neoplasias depende entre otras cosas de la población en estudio, parece lógico separar dentro de la población oncológica a aquellos pacientes que debutan con un cáncer y que se realizan un PET de etapificación, de aquellos con una malignidad ya tratada y en seguimiento, ya que muchos de estos últimos han recibido terapias que pueden predisponer la aparición de nuevas neoplasias [10][11][12] . En los pacientes con cáncer de reciente diagnóstico, la ocurrencia de neoplasias sincrónicas insospechadas reportada en la literatura fluctúa entre 1,7 y 17,6 % de los individuos que se realizan Cáncer sincrónico y metacrónico detectado con PET/CT -D. Ladrón de Guevara et al un PET/CT corporal 7,8,[13][14][15][16][17] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ya que la frecuencia de ocurrencia de neoplasias depende entre otras cosas de la población en estudio, parece lógico separar dentro de la población oncológica a aquellos pacientes que debutan con un cáncer y que se realizan un PET de etapificación, de aquellos con una malignidad ya tratada y en seguimiento, ya que muchos de estos últimos han recibido terapias que pueden predisponer la aparición de nuevas neoplasias [10][11][12] . En los pacientes con cáncer de reciente diagnóstico, la ocurrencia de neoplasias sincrónicas insospechadas reportada en la literatura fluctúa entre 1,7 y 17,6 % de los individuos que se realizan Cáncer sincrónico y metacrónico detectado con PET/CT -D. Ladrón de Guevara et al un PET/CT corporal 7,8,[13][14][15][16][17] .…”
Section: Discussionunclassified
“…Se definió cáncer metacrónico a una segunda neoplasia maligna diagnosticada entre 6 meses y 10 años después del diagnóstico del primer cáncer 2,3,10 .…”
Section: Definición De Cáncer Sincrónico Y Metacrónicounclassified
“…A study in Japan reported that the esophagus, ovary, larynx, pharynx and mouth were the most frequent sites for developing a second primary cancer (21). In Queensland, Australia, from 1997 to 2001, second primary cancers of the head and neck were frequent, whereas those of the esophagus and ovary were not as common (22).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of second cancers has increased (21)(22)(23). A study on data from the European Cancer Registry reported an overall incidence of double primary cancer of 6.3% (range, 0.4-12.9%) (24); Utada et al reported that the proportion of patients with a second primary tumor during the follow-up period was 8.1% (median, 1.8 years; mean, 4.3 years) (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation